2018
DOI: 10.1002/advs.201800866
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Iron Deposition Profiles of Liver Zones in Various Models with Iron Homeostasis Disorders

Abstract: Determination of iron accumulation is crucial in diagnosing the occurrence and progression of many liver‐ and iron‐related diseases. Thus far, little is known about the profiles of iron deposition in different liver zones, particularly under conditions with disordered iron homeostasis. Here, uneven iron distribution in livers of patients with hereditary hemochromatosis (HH) is uncovered, showing the region with the highest iron concentration near the entrance site of the portal vein and hepatic artery in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…An older study reported already in 1982 a significantly lower 59 Fe-RBCIU in healthy aged subjects 14 days after an oral iron test dose, while RBCIU after an intravenous dose showed no difference [25]. In this small study RBCIU upon intravenous iron could not be measured in the same subjects as RBCIU upon oral iron administration.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…An older study reported already in 1982 a significantly lower 59 Fe-RBCIU in healthy aged subjects 14 days after an oral iron test dose, while RBCIU after an intravenous dose showed no difference [25]. In this small study RBCIU upon intravenous iron could not be measured in the same subjects as RBCIU upon oral iron administration.…”
Section: Discussionmentioning
confidence: 62%
“…Presented values are medians with interquartile ranges (IQR). Iron uptake, retention and transfer were calculated from the amount of 59 Fe and 51 Cr in the body 24 h after the oral iron test dose (uptake) and 14 days after the oral iron test dose (retention). Mucosal iron transfer is the fraction of iron retained after uptake.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations